ANALISIS DAN PERANCANGAN SISTEM INFORMASI REKAM MEDIS PADA KLINIK AKPER KESDAM II/SRIWIJAYA GARUDA PUTIH - Sinaga, Rudolf; Nurhadi, Nurhadi (Jurnal Manajemen Sistem Informasi, 2016)
Clinic of Akper Kesdam II/Swj Garuda Putih located at RT.12 Desa Suak Kandis KM.17, Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi. Currently patient enrollment, there was a queue when the number of patients who will be treated to increase, due to the manual search of medical records still are looking for in the storage closet that takes about 3-5 minutes. In making the report also need the time because the source of the report used to use paper media. So that the report made no ready when requested by the manager. Source reports can also be lost, the impact generated report becomes inaccurate. Based on the above problems, the solution is made is to design and build applications that can help manage patient data and preparing reports on Clinic of Akper Kesdam II/Swj Garuda Putih. With this application, is expected to reduce the queues that accumulate while the number of patients who come increased so as to accelerate the registration process. This application is also expected to accelerate the creation of reports required by the Clinic of Akper Kesdam II/Swj Garuda Putih.